P11.34.A Pseudoprogression in cases of brain metastases and its neurooncological pitfalls under PD-1 inhibitor therapy in the era of personalized medicine. (5th September 2022) - Schulz, T; Cattaneo, A; Löhr, M; Dufner, V; Monoranu, C; Keßler, A
Abstract: Background: Immunotherapy plays an increasing role in combating malignant cancers. Recently, there has been a noticeable uptick of pseudoprogression mimicking true tumor growth or even intracranial abscess. PD-1 inhibitors especially have come under scrutiny for imitating progressive diseases. Here, we summarize our departmental findings to this regard. Material and Methods: We analyzed the clinical, intraoperative and neuropathological findings as well as perioperative radiological imaging in four cases. Results: Four patients (three males and one female, ranged 52-74 years) underwent resection for brain metastases and were subsequently treated with radiotherapy and with PD-1 inhibitors. Within one-year post-surgery, cranial MRI-imaging showed space-occupying, contrast enhanced lesions in all four patients. In two cases FET-PETs were performed pre-operatively. They showed a significant increase in aminoacid uptake. In two cases, 5-aminolevulineacid (5-ALA) was applied pre-operatively. In one case, there was considerable 5-ALA uptake. The fourth patient presented radiological signs of an abscess and underwent emergency surgery. The neuropathological workup of all tissues in question depicted highly increased activity of lymphocytes and microglia, accompanied by necrosis. All cases were classified as pseudoprogression, which, on top, had developed supramarginally in previously healthy tissue. Conclusion: Neurooncologists face crescent challenges in the increasing cases of pseudoprogression under/after immunotherapy. Radiological imaging doesn't seem to be able to clearly differentiate between true and pseudoprogression. Even FET-PETs, in general a valid diagnostic tool, seem to be fooled by checkpoint inhibitors. Furthermore, pseudoprogressive tissue after PD-1 inhibitor therapy might mimic tumor tissue intra-operatively by increased 5-ALA uptake. All these characteristics increase the risk of overly aggressive resection of the suspected cancerous or infectious, but in the end pseudo-progressive tissue. Brain edema and clinical symptoms spurred by pseudoprogression may be an indication for surgery, but the risk of performing possibly unnecessary surgery based on radiological findings fooled by PD-1 inhibitors should be taken into consideration. At this point, there does not seem to be a foolproof diagnostic method to differentiate pseudo- from true progression. And there is the possibility that the pseudoprogression is happening in tissue adjacent to the previously resected lesion. Neurooncologists need to acknowledge that pseudoprogression under/after immunotherapy will become only more prevalent in the future and take this message to their patients.